Application of New Empirical Algorithm in Coastal Waters of Padanggalak Beach to Detect Total Suspended Solid Value - Astiti, Sagung Putri Chandra; Dharma, I Gusti Bagus Sila; Pariartha, I Putu Gustave Suryanthara; As-Syakur, Abd. Rahman; Arsana, I Gusti Ngurah Kerta (ASTONJADRO, 2026)
Total Suspended Solid is one of the important indicators in the physical parameters to determine the quality status of the waters studied. In this case, researchers will create a new algorithm to detect TSS values ​​at Padanggalak Beach, where the beach is the estuary of the Ayung Watershed. The creation of the algorithm that has been carried out by several researchers took the case in coastal waters, so that the algorithm will cause a fairly high difference in value when applied to other coastal areas. Coastal areas in each place have different characteristics, where coastal areas are dynamic areas, influenced by various factors including climate, weather, wind direction, ocean currents and characteristics of the use of the surrounding environment. Field data taken in the form of seawater samples were then tested in the laboratory to produce TSS concentration values ​​at each sample point. Field observations for TSS sampling in the coastal waters of the Ayung DAS estuary located at Padanggalak Beach were carried out on Wednesday, August 14, 2024 at 08.00 - 10.30 WITA. The form of the new algorithm equation produced along with its correlation level is TSS = -25.096 x (B6/B11) + 42.415, for TSS estimation at Padanggalak Beach. Based on the results of the analysis of the determination coefficient of the New Empirical TSS Algorithm with Insitu TSS, the R2 result was 0.6812. This shows that the results of in situ data and the results of satellite image processing using the New Empirical Algorithm are considered to have a strong correlation relationship, which means that the TSS results from the empirical algorithm are quite in accordance with the TSS results in the field at the Ayung DAS Estuary (Padanggalak Beach).